Combined economic and emission dispatch using intelligent water drops-continuous optimization algorithm - Nagalakshmi, P.; Harish, Y.; Kumar, R. K.; Jada, C. (2011 International Conference on Recent Advancements in Electrical, Electronics and Control Engineering, 2011)
This paper presents a new optimization technique IWD-CO to solve an optimization problem Combined Economic and Emission Dispatch (CEED). The CEED is a combination of Economic Load Dispatch and Emission Dispatch which aims at minimization of the fuel cost and emission cost of generating units while satisfying the load conditions and other constraints. The present algorithm is inspired from the natural river dynamics. Here the agents are water drops and they are used to find the optimal path in the search space. The IWD-CO is used in an efficient manner to solve large generating unit power system. The results of the IWD-CO to solve CEED are tested with 3 and 6 generator power systems and they are satisfactory. IWD-CO results are also compared with the Genetic Algorithm (GA) and Particle Swarm Optimization (PSO) to show the effectiveness of algorithm.